Surgical pathology of the thymus: 20 years' experience. Issue 1 (January 1986) - Large, S R; Shneerson, J M; Stovin, P G; Wallwork, J
Abstract : Fifty five patients underwent thymic surgery at Papworth Hospital from April 1964 to March 1984. The number presenting and the percentage with symptoms annually remained unchanged during this period. Forty four of these 55 patients had tumours. Twenty eight had thymomas (18% of whom had myasthenia gravis and 7% red cell aplasia), nine Hodgkin's disease, four germ cell tumours, and three secondary carcinomatous tumours. Five tumours were cystic. Six further patients had non-tumourous cystic lesions (four simple, one foregut, one lymphangiectatic). The remaining five patients had follicular hyperplasia; all of these had myasthenia gravis. Complete excision was performed in 41 of the 55 patients. So far survival is 100% in those with benign lesions other than benign thymomas, where the survival was 70% at five years. Those with malignant thymomas had a 60% survival rate at five years and those with Hodgkin's disease 29%.